2009
DOI: 10.1186/1472-6963-9-81
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Social Capital in Hospitals and Physician Job Satisfaction

Abstract: BackgroundJob satisfaction in the hospital is an important predictor for many significant management ratios. Acceptance in professional life or high workload are known as important predictors for job satisfaction. The influence of social capital in hospitals on job satisfaction within the health care system, however, remains to be determined. Thus, this article aimed at analysing the relationship between overall job satisfaction of physicians and social capital in hospitals.MethodsThe results of this study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 55 publications
(47 reference statements)
4
84
0
4
Order By: Relevance
“…Researchers tend to agree that closed ties with coworkers are positively related to professionals' satisfaction: In hospital-based units, network closure boosted positive nurses' perceptions of organizational climate, which in turn buffered nurses from the negative effects of work stress (Garrett & McDaniel, 2001). Nurses receiving low support from coworkers reported low job satisfaction and low self-rated health (Lindholm et al, 2003); but it is of interest to note that the social support received by coworkers was unrelated to job satisfaction for both physicians and nurses occupying managerial roles (Lindholm, 2006;Lindholm et al, 2004) recent study suggested a more nuanced set of relations between job characteristics, social support and job satisfaction: social support received from coworkers, in addition to professional experience and work load, was shown to predict physicians' job satisfaction (Ommen et al, 2009). An interesting and almost unexplored area of research concerns the extent to which job satisfaction relates to network dynamics, in terms of creation, preservation, and dissolution of interpersonal ties with coworkers.…”
Section: Satisfaction At Workmentioning
confidence: 99%
“…Researchers tend to agree that closed ties with coworkers are positively related to professionals' satisfaction: In hospital-based units, network closure boosted positive nurses' perceptions of organizational climate, which in turn buffered nurses from the negative effects of work stress (Garrett & McDaniel, 2001). Nurses receiving low support from coworkers reported low job satisfaction and low self-rated health (Lindholm et al, 2003); but it is of interest to note that the social support received by coworkers was unrelated to job satisfaction for both physicians and nurses occupying managerial roles (Lindholm, 2006;Lindholm et al, 2004) recent study suggested a more nuanced set of relations between job characteristics, social support and job satisfaction: social support received from coworkers, in addition to professional experience and work load, was shown to predict physicians' job satisfaction (Ommen et al, 2009). An interesting and almost unexplored area of research concerns the extent to which job satisfaction relates to network dynamics, in terms of creation, preservation, and dissolution of interpersonal ties with coworkers.…”
Section: Satisfaction At Workmentioning
confidence: 99%
“…His efforts were pursued by Putnam in Europe and the theory of social capital was developed with the theories of Coleman and Putman (Samimi et al, 2009). Up to now, the relationships between social capital and numerous variables, such as quality of life (Nillson et al, 2006) trust, awareness and occupational satisfaction (Ommen et al, 2009), improved wellbeing and diminished poverty (Woolcock and Narayan, 2006), health and quality of life in workplace (Chen et al, 2010) have been demonstrated in many studies. Social capital creates collaboration, commitment, data sharing and trust.…”
Section: Introductionmentioning
confidence: 99%
“…Eine Studie unter Krankenhausärzten ergab, dass ein als gering wahrgenommenes Sozialkapital signifi kant positiv mit Burnout von Ärzten assoziiert war [ 23 ] . Darü-ber hinaus zeigte sich, dass Sozialkapital einen beträchtlichen positiven Einfl uss auf die allgemeine Arbeitszufriedenheit von klinisch tätigen Ärzten hat [ 24 ] . Der Zusammenhang von Sozialkapital und Engagement fand in der Forschung nach dem Kenntnisstand der Autoren noch keine Beachtung.…”
Section: Sozialkapital Und Work Engagementunclassified